(3GdebGeGJ GdRjfjIs - (3eYO Hf fUQ Gddg Hf QLH, CHh GdfOj TeS GdOjf GHf CHj GdaJM, GdeYQha HGHf GdUjbd GdLRQj,J (B701 (3g` s
(3ChdgG (B:s
(3CKfGA GdebGeI GdQGHYI bhdg(B: (3dTHd GdTejPQ GdYHTej, djTGgO TMP TaQJg s
(3BNQgG (B:s
(3haVJ CbajJg agGVJ hfVQ aVdg aGQVi hfgV dEeVGFg GdJVdjY s
(3fSNI KGdKI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B304 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B465s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B84 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1785s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs